Women in Bangladesh Liberation War - Chowdhury, Selima (Bangladesh National Museum, 2018)
Research study on the Madonna series of Rokeya Sultana
Originally presented as the author's thesis: SOAS, University of London
Keywords: Hochschulschrift; Sultana; Rokeya; Women